A metallic peanut-shaped carbon nanotube and its potential for CO2 capture. (June 2018) - Zhao, Tianshan; Wang, Qian; Kawazoe, Yoshiyuki; Jena, Puru
Abstracts: One of the greatest challenges in greenhouse gas reduction is to develop low-cost materials capable of efficient CO2 capture. Carbon, due to its flexible bonding characteristics, numerous allotropic forms, and lightweight, is an attractive material for such investigation. Inspired by the experimental synthesis of C50 Cl10 in milligram quantities and recent works on peanut-shaped carbon nanotubes (PSNT), using state-of-the-art first-principles theory and molecular dynamics simulation, we have discovered a new form of C50 fullerene-based PSNT, α-PSNT. which is not only dynamically and thermally stable, but also energetically more stable than previously identified PSNTs composed of C50 cages, and can withstand temperatures to 1000 K. Due to its unique atomic configuration, α-PSNT exhibits interesting physical properties including a high heat capacity, ultra-soft mechanical property with Young's modulus being a quarter of single-walled carbon nanotube (SWNT), and chirality independent metallicity. A systematical study of the adsorption properties reveals that both pristine and N-doped α-PSNTs have better CO2 adsorption properties than SWNTs. The underline mechanism is that the intrinsic metallicity improves its ability to capture CO2 as well as other gases because of the high density of electronic states at the Fermi level. Graphical abstract: Image 1